Implementasi Standar Prasarana di SMAN Se-Kecamatan Koto Tangah Padang - Ridha Nabila; Syahril Syahril; Ahmad Sabandi; Yulianto Santoso (Journal of Educational Administration and Leadership, 2021)
This study aims to describe the suitability of existing infrastructure in schools with predetermined standards. This research is a descriptive study with qualitative methods. Data werecollected using interview, observation (observation) and documentation study. Data analysis using interactive analysis techniques include data reduction, data presentation and drawing conclusions. For data validity using triangulation technique. The result stated that (1) sman classroom (7,8,13) Padang were appropriate, (2) sman library room (7,8,13) field is very suitable, (3) sman biology laboratory room (7,8,13) field is very suitable, (4) the physics laboratory room of SMAN (7,8,13) the field is very suitable, (5) the chemistry laboratory room of SMAN (7,8,13) the field is very suitable, (6) the computer laboratory room of SMAN (7,8,13) the field is very suitable, (7) the laboratory room of sman language (7,8,13) the field is not suitable, (8) sman leadership room (7,8,13) field is very suitable, (9) sman teacher room (7,8) appropriate field, SMAN 13 field is not suitable, (10) SMAN administration room (7,8,13) field is very suitable, (11) THE place of worship of SMAN (7,8,13) of the field is very suitable, (12) the counseling room of SMAN (7,8,13) of the field is very suitable, (13) the uks sman room (7,8,13) the field is very suitable , (14) the student organization room of SMAN 13 padang is very suitable, SMAN (7,8) field is not suitable, (15) latrine / toilet SMAN (7,8,13) appropriate field, (16) SMAN warehouse 13 fields are very suitable, SMAN 8 appropriate fields, SMAN 7 fields are not suitable, (17) circulation space SMAN (7,8,13) appropriate fields, (18) playgrounds / sports SMAN 13 fields are very suitable, SMAN (7.8) fields in accordance with the infrastructure standards set out in PermendiknasNumber 24 of 2007.